Kompetensi supervisi kepala sekolah Dalam pengembangan keprofesian berkelanjutan - Muhammad Yusuf; Yusra Jamali (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Abstract The principal has a strategic role in developing and intensifying teachers’ competencies, including sustainable professional development. The Principal is under an obligation to provide guidance, assistance, assessment and supervision to teachers related to the organization and development of pedagogical skills. An appointed principal with qualified supervisory skill in carrying out these duties is necessary to accomplish the guidance and supervision processes technically in well-balanced, stable and dynamic. Supervision responsibility can be actually carried out anytime and anywhere, but in an educational organization system, supervisors should be directly presented in controlling the continual direction and guidance for the development of teachers objectively. Sustainable professionalism development for professional teachers can be emphatically actualized by providing proper awards, teacher certification, education and training, provision of learning facilities, equal distribution of teaching and learning hours, and provision of incentives based on their duties and responsibilities. Endorsements of sustainable professionality development for professional teachers consist of self-development, scientific publications, and or innovative works. Every supervision result needs to be ceaselessly followed up with an ongoing evaluation in order to get a solution in achieving the improvement of teachers’ professionalism. Abstrak Kepala sekolah mempunyai peran strategis dalam upaya pengembangan dan peningkatan kompetensi guru, termasuk pengembangan keprofesian berkelanjutan. Kepala Sekolah bertugas memberikan bimbingan, bantuan, pengawasan dan penilaian kepada guru terkait dengan penyelenggaraan dan pengembangan pendidikan pengajaran. Kepala sekolah dalam melaksanakan tugasnya, dengan kompetensi supervisi dapat melakukan proses pembinaan dan pengawasan secara seimbang, stabil dan dinamis. Tugas supervisi sesungguhnya dapat dilaksanakan kapan saja dan di mana saja, tetapi dalam sistem organisasi pendidikan, supervisor perlu hadir secara langsung untuk memberi arahan dan pembinaan secara objektif. Upaya pengembangan keprofesian berkelanjutan bagi guru dapat dilakukan dalam bentuk penghargaan, sertifikasi guru, pendidikan dan pelatihan, penyediaan fasilitas pembelajaran, pemerataan jam pembelajaran, pemberian insentif sesuai beban tugas dan tanggungjawabnya. Penguatan pengembangan keprofesian berkelanjutan bagi guru, meliputi pengembangan diri, publikasi ilmiah, dan karya inovatif. Setiap hasil supervisi perlu ditindaklanjuti agar mendapatkan solusi dalam rangka peningkatan profesionalisme guru.